Decompression of the Jugular Bulb for Enhanced Infralabyrinthine Access to the Petroclival Region: A Quantitative Analysis - Miller, Matthew; Pearl, Monica S.; Wyse, Emily; Olivi, Alessandro; Francis, Howard W. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objectives To describe an enhanced infralabyrinthine approach to petroclival lesions with jugular bulb decompression, and to quantify surgical access using a flat-panel computed tomography image protocol.Design Retrospective case series and paired comparison of pre- versus post-dissection anatomy.Setting Tertiary academic medical center.Participants Four patients presenting with petroclival lesions. Six fresh cadaveric specimens were used for temporal bone dissection.Main Outcome Measures Axial and coronal dimensions, and access angles of the infralabyrinthine surgical corridor.Results Decompression of the jugular bulb increased the craniocaudal width of the infralabyrinthine corridor from 0.9 to 7.9 mm to 6.5 to 11.6 mm. The mean increase of 4 mm was statistically significant (t = 3.7; p < .05). There was also a significant widening of the infralabyrinthine window along the axial dimension by 0.9 to 4.5 mm or a mean of 2 mm (t = 3.7; p < .05). Angles of access to the petroclival region were wider following jugular bulb decompression, particularly in the coronal plane (mean difference 7.9 degrees; t = 5.0; p < .005) but less so in the axial plane (mean difference 4.7 degrees; t = 2.5; p = .05).Conclusions Jugular bulb decompression enhances infralabyrinthine access to petroclival lesions, permitting the removal of tissue for diagnoses or partial resection, without significant additional morbidity.
Keywords: petroclival junction; transtemporal approach; jugular bulb decompression; flat-panel computed tomography